Роль плотности популяции в динамике численности непарного шелкопряда в Нижнем Приднепровье - Киреева, И.М. (Вестник зоологии, 1978)
It was determined by experiments that when the population density reaches 10 individuals per breeding cage (55X42X55 cm) a considerable part of caterpillars acquires all morphological and physiological characters of the dark-coloured individuals. Consequently the population density is significant in appearance of different morphological types of caterpillars which have their own physiological properties and possess different viability, that is of great importance for the number regulation process in the Porthetria dispar 1.. population in the Lower Dnieper area.